Adaptability and Survivability of Different Crossbreds cattle under Commercial Dairy Farming Conditions in Chittagong area (International Journal of Natural Sciences, 2012)
The present study was undertaken to investigate the adaptability and survivability of different crossbred dairy cows under commercial farming conditions in Chittagong, Bangladesh. Different cattle genotypes (Holstein × Local, Sahiwal × Local, Sahiwal × Holstein and Jersey × Local) were found in the studied farms. The percentages of Holstein × Local was (58.94%) higher than other genotype. The survivability of Holstein × Local, Sahiwal × Local, Sahiwal × Holstein and Jersey × Local calves were 84.0±3.90, 100, 97.1±5.48 and 100 percent, respectively. The survivability of calves and cows were significantly different (P